ASUHAN KEPERAWATAN GERONTIK PADA NY. E DENGAN PENERAPAN TERAPI REMINISCENCE UNTUK MENINGKATKAN FUNGSI KOGNITIF PADA LANSIA DENGAN DEMENSIA DI PANTI WERDHA YAYASAN TRUE LOVE KOTA BATAM - Putri, Nur Hafizah; Gemini, Savitri (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Problems that are often faced by the elderly as time goes by, they experience a decline in cognitive function. This Professional Scientific Paper aims to provide Gerontic Nursing Care to Mrs. E through the application of reminiscence therapy to improve cognitive function in the elderly with dementia at the True Love Foundation Nursing Home in Batam City. The method used in this Professional Scientific Paper is a case study. The results of the assessment obtained by the client complained that the older he got, he easily forgot, the client said that it was difficult to remember behavior that had been done before, from the results of the assessment, the client appeared confused when given several, from the results of the SPMSQ showed a value of 6 which means moderate intellectual impairment, seen during the assessment (MMSE) with a total value of 17 which means probable cognitive impairment. With a nursing diagnosis of memory disorders related to the aging process. The intervention and implementation given were in the form of reminiscence therapy for 9 days. The results of the final evaluation of nursing care for Mrs. E were obtained. E with cognitive impairment in dementia, the patient said there was a change after reminiscence therapy, he began to remember a lot, it seems the patient has remembered a lot and told about his past from the results of the cognitive function assessment using SPMSQ showed a value of 2 which means intact intellectual damage, it was seen during the mini mental state exam (MMSE) assessment with a total value of 22 which means normal. The conclusion from the nursing results was that there was an improvement after being given therapy, and reminiscence therapy is effective in improving cognitive function.. Keywords: Cognitive disorders, Dementia, Nursing care with reminiscence therapy